A multi-step method for partial eigenvalue assignment problem of high order control systems. (15th September 2017) - Liu, Hao; Xu, Jiajia
Highlights: We propose a multi-step method for solving the partial eigenvalue assignment problem of high order systems. We give the solvable condition and the explicit solutions to the partial eigenvalue assignment problem of high order systems. Our algorithm is easy to realize and effective. Abstract: In this paper, we consider the partial eigenvalue assignment problem of high order control systems. Based on the orthogonality relations, we propose a new method for solving this problem by which the undesired eigenvalues are moved to desired values and keep the remaining eigenvalues unchanged. Using the inverse of Cauchy matrix, we give the solvable condition and the explicit solutions to this problem. Numerical examples show that our method is effective.